Teologi Perdamaian dan Kerukunan Antar Agama dalam Perspektif Asghar Ali Engineer - Saumantri, Theguh (Jurnal Pemikiran Islam, 2023)
This article explores the concept of Islamic theology of peace and interfaith harmony through the perspective of Asghar Ali Engineer, particularly focusing on the essence of Islam, theology of peace, and interreligious harmony. The article employs a literature study method, analyzing and interpreting Engineer's works. Asghar Ali Engineer, an Indian Muslim scholar and intellectual, advocates for peace and pluralism in Islam, emphasizing the importance of Tauhid (the Oneness of God) as a foundation for social justice and peace. His approach integrates the concept of liberation theology, emphasizing the necessity of liberating humanity from oppression and injustice. Engineer interprets Tauhid not merely as a religious ritual but as a social structure that fosters equality and peace. He argues that true peace in Islam involves respecting religious diversity and eliminating coercion in faith. The study affirms that Engineer's theology of peace is relevant in multicultural and multireligious contexts like Indonesia and can offer an alternative approach to resolving interfaith conflicts. Engineer's emphasis on dialogue and understanding among different faiths is crucial for enhancing harmony and reducing societal polarization.AbstrakArtikel ini mengeksplorasi konsep teologi perdamaian Islam dan kerukunan antaragama melalui pemikiran Asghar Ali Engineer, khususnya mengenai esensi Islam, teologi perdamaian, dan kerukunan antar agama. Artikel ini menggunakan metode studi pustaka dengan menganalisis karya-karya Engineer dan menginterpretasikannya. Asghar Ali Engineer, seorang ulama dan intelektual Muslim India, mengadvokasi perdamaian dan pluralisme dalam Islam, menekankan pentingnya Tauhid (Keesaan Allah) sebagai dasar untuk keadilan sosial dan perdamaian. Pendekatannya menggabungkan konsep teologi pembebasan, menekankan pentingnya membebaskan umat manusia dari penindasan dan ketidakadilan. Engineer menafsirkan Tauhid tidak hanya sebagai ritual agama tetapi sebagai struktur sosial yang mendorong kesetaraan dan perdamaian. Ia berargumen bahwa perdamaian sejati dalam Islam melibatkan penghormatan terhadap keragaman agama dan penghapusan paksaan dalam beragama. Kajian ini menegaskan  bahwa teologi perdamaian Engineer relevan dalam konteks multikultural dan multireligius seperti di Indonesia dan dapat menjadi pendekatan alternatif untuk mengatasi konflik antar agama. Penekanan Engineer pada dialog dan pemahaman antar agama yang berbeda sangat penting untuk meningkatkan kerukunan dan mengurangi polarisasi masyarakat.